Modern Techniques and Technology (MTT' 2001) proceedings of the 7th International Scientific and Practical Conference of Students, Post-graduates and Young Scientists, Tomsk, Febrary 26-March 3, 2001 ([S. I.], IEEE, 2001)
Title screen